Black Feminist Resistance in Hidden Figures (2016) Film: Applying Patricia Hill Collins’ Theory - Gilang Hardian (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2026)
This research analyzes feminist values in Hidden Figures (2016), a film portraying the experiences of three African American women—Katherine G. Johnson, Dorothy Vaughan, and Mary Jackson—who contributed significantly to NASA (National Aeronautics and Space Administration) during the 1960s. Despite their achievements, these women faced systematic discrimination based on both race and gender. This research aims to identify feminist values within the film through the lens of Patricia Hill Collins’ Black Feminist Theory, supplemented by a post-nationalist theory. Post-nationalist theory helps reinterpret American identity by centering the voices of marginalized groups, particularly Black women, whose contributions are frequently overlooked in mainstream narratives. A qualitative method is used, the research focuses on key scenes, dialogues, and character development. The analysis reveals core feminist values such as self-definition, independence, solidarity, and resistance to oppression. These values reflect how Black women in the movie challenge racial and gender-based inequalities while asserting their identity and agency. The findings show that Hidden Figures not only celebrates individual empowerment but also promotes a broader understanding of equality and social justice. This research contributes to feminist and cultural studies by showing how movies can be a powerful tool for representing underrepresented voices and reshaping national identity through inclusive narratives. Abstrak Penelitian ini menganalisis nilai-nilai feminis dalam film Hidden Figures (2016), yang menggambarkan pengalaman tiga perempuan Afrika-Amerika, yaitu Katherine G. Johnson, Dorothy Vaughan, dan Mary Jackson, yang memberikan kontribusi signifikan bagi NASA (National Aeronautics and Space Administration) pada tahun 1960-an. Meskipun telah meraih berbagai prestasi, mereka tetap menghadapi diskriminasi berdasarkan ras dan gender. Penelitian ini bertujuan untuk mengidentifikasi nilai-nilai feminis dalam film tersebut menggunakan Teori Feminis Hitam karya Patricia Hill Collins, yang didukung oleh teori pasca-nasionalis. Teori pasca-nasionalis membantu menafsirkan kembali identitas Amerika dengan memusatkan suara kelompok-kelompok yang terpinggirkan, terutama wanita kulit hitam, yang kontribusinya sering diabaikan dalam narasi arus utama. Metode kualitatif digunakan, dengan fokus pada adegan, dialog, dan pengembangan karakter. Analisis mengungkapkan nilai-nilai feminis inti seperti penentuan diri, kemandirian, solidaritas, dan perlawanan terhadap penindasan. Nilai-nilai ini mencerminkan bagaimana perempuan kulit hitam dalam film tersebut menantang ketidaksetaraan rasial dan gender sambil menegaskan identitas dan otonomi mereka. Temuan ini menunjukkan bahwa Hidden Figures tidak hanya merayakan pemberdayaan individu, tetapi juga mempromosikan pemahaman yang lebih luas tentang kesetaraan dan keadilan sosial. Penelitian ini berkontribusi pada studi feminis dan budaya dengan menunjukkan bagaimana film dapat menjadi alat yang ampuh untuk mewakili suara-suara yang kurang terwakili dan membentuk kembali identitas nasional melalui narasi yang inklusif.